Development of innovationin the Polish banking sector - Polkowska, Zofia (Research Papers in Economics and Finance, 2024)
The rapidly developing market for new technologies is driving the introduction of innovative solutions in the banking sector. As a public trust sector, they are subject to numerous regulations. Supervisors and central banks are trying to support the develop- ment of new technologies in the sector by reducing regulatory uncertainty and support programs aimed at FinTech (Financial Technologies) companies. The purpose of the study is to analyse existing regulations and regulators’ initiatives on new technologies in the banking sector. The author seeks to answer the research question of whether the introduced regulations support or limit the digital transformation of the banking sector in Poland. An im- portant aspect in the sector is customer security, so regulations should focus on protecting the banking customer and ensuring the stability of the sector. They are analysed by regulators so that the relevant regulations enable the introduction of innovative yet safe solutions. The author points out possible synergies resulting from cooperation between banks and FinTech companies. In conclusion, dialogue between banking sector institutions, regulators, central banks and banks leads to the creation of an environment that allows the introduction of innovative solutions while maintaining customer protection and banking sector stability.